Secrets of solid state and aqueous solution structures of [Ni(tmdta)]2- - Meier, Roland; Linti, Gerald W. (Inorganic chemistry, 2014)
The molecular structures of Li2[Ni(tmdta)]·5H2O (1a, tmdta = trimethylenediaminetetraacetate), {C(NH2)3}2[Ni(tmdta)]·6H2O (1b), and {Ni(H2O)6}[Ni(tmdta)]·2H2O (2a) have been determined. The central trimethylenediamine chelate ring shows half-chair (hc) geometries in 1a and 1b, while a twist-boat (tb) conformation is encountered in 2a. The coexistence of tb and hc forms in the solid state prompted us to elucidate the existence of a tb ⇌ hc equilibrium in aqueous solution. Evaluation of the data from solid state vibrational spectra (Raman and IR) for the hc and tb forms showed excellent agreement with simulated spectra obtained with DFT computations (TPSSh/TZVP). This outstanding matching between theory and experiment enabled us to build composite spectra with varying hc:tb ratios. Comparison of these results with Raman and IR spectra recorded for [Ni(tmdta)]2- in aqueous solution revealed that simulated Raman and IR spectra with a hc:tb ratio = 2:3 match the solution spectra in an accurate way. This equilibrium ratio enabled us to compute 13C NMR sifts for the paramagnetic solution spectrum of [Ni(tmdta)]2- based on the relative contributions by hc and tb fractions. This leads to computed shifts that agree closely with the experimental ones. Also, the kinetics of the skeleton dynamics could be estimated quantitatively by temperature-dependent 13C NMR spectroscopic measurements. An interesting effect encountered for the very first time here concerns a drastic intensity difference of the 10Dq band (3A2g → 3T2g(F) transition) in solid state electronic spectra of tb vs hc isomers, where the intensity of this band in the case of the hc form is much lower than that of the tb conformer and thus more similar to the case of the usual NiII chromophore in octahedral environment. The equilibrium constants for complex formation and protonation of NiII-tmdta at low pH have been estimated by pH-dependent UV-vis titration experiments. Correlation of these data with those of NiII-edta and related 3d MII edta and tmdta complexes allow important conclusions on the consequences resulting from extending the central diamine ring in the ligand by one methylene group in terms of both complex and protolytic stability for edta vs tmdta complexes.